The effectiveness of using language games in developing and supporting language patterns in the Arabic language among third-grade primary students in government schools at the Maraka - Hawalta, Rajaa Yousef (Journal of Educational and Psychological Sciences, 2021)
The researcher has conducted a study aimed at identifying the effectiveness of using language games in developing and supporting language patterns among third-grade primary students in government schools at the Maraka. Females and two groups of male and female students. also. were chosen intentionally. depending on the choice of the two schools. The two experimental groups were taught using language games. while the two control groups were studied using the regular direct method based on instruction between the teacher and the student. The researcher built an achievement test consisting of (20) items. The results of the study revealed the presence of statistically significant differences at the level (α = 0.05) between the students of the control group and the students of the experimental group due to the effect of teaching using language games (Female. male). At the end of the research. the researcher put forward a set of recommendations. such as diversifying teachers in teaching strategies and methods in a manner commensurate with the different learning styles of their students. in addition to - training teachers. on how to use language games to develop linguistic patterns and benefit from it in introducing students to their preferred linguistic patterns.